Biovalorization of glucose in four culture media and effect of the nitrogen source on fermentative alcohols production by Escherichia coli. Issue 2 (15th January 2020) - Fernández-Gutierrez, David; Veillette, Marc; Ávalos Ramirez, Antonio; Giroir-Fendler, Anne; Faucheux, Nathalie; Heitz, Michèle
ABSTRACT: Glucose is one of the most abundant monosaccharides and the easiest carbon source to be consumed by bacteria. In this study, four culture media (LB, M9, M63 and MOPS) were supplemented with glucose at three different concentrations (4, 12.5 and 25 g/L) in the presence of a genetically modified strain of Escherichia coli with the purpose of selecting the most suitable culture medium to obtain ABD (acetoin (A) and 2, 3-butanediol (2, 3-BD)). The selected medium was M9, the cheapest culture medium, since the ABD yields obtained fermenting 12.5 and 25 g/L of glucose in M9 culture medium at 37°C, atmospheric pressure, initial pH 6.5, 100 rpm and 10% (v/v) of inoculum were similar compared to the ABD yields obtained using M63 and LB culture media. The influence of nitrogen on ABD yield was tested adding sodium nitrate (NaNO3 ) or urea ((NH2 )2 CO) to M9 culture medium at three different nitrogen concentrations (2.5, 5.0 and 7.0 g N/L). Adding urea (7.0 g N/L) to M9 supplemented with 25 g/L of glucose improved by 23% the ABD yield at 96 h compared to M9 without urea, reaching a value of 27.2% (g ABD/g glucose). In contrast, the use of NaNO3 had no significant effect on the ABD yield. GRAPHICAL ABSTRACT: